Water availability in Water-economic basins in Kazakhstan and their Anthropogenic transformation (Journal of Geography and Environmental Management, 2018)
Water is one of the most important natural resources. The water availability and scarcity depend on various natural and anthropogenic factors. On the basis of generalization and analyses of the numerous cartographic materials, the water-economic basins (WEBs) in Kazakhstan were classified in order to identify the basin affected by human activities the most. Additionally, the water supply (availability) in the WEBs was determinated by share (%) of water resources (rivers, lakes, water reservoirs). The Zhaiyk-Caspian WEB has the highest share (94%) of river water. By water resource (43.8 km3), the Ertis WEB is the most water-rich basin. A significant anthropogenic transformation was observed in the Aral-Syrdarya and Esil WEBs. Both basins are characterized by water pollution and a deteriorated water quality.